CORROSION RATE COMPARISON OF LOW-CARBON PIPES STEEL IN VARIOUS AGGRESSIVE ENVIRONMENTS - PETRYNA, DMYTRO (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Low-carbon steel is the main material for the production of main oil and gas pipelines. Currently, X70, X80 type steels are used in world practice, however pipelines that have been in operation for more than 45 years were made of 17Г1C (X50, X52) steels. Steels of the new generation X100 and X120 have improved strength indicators and therefore they are increasingly used for the manufacture of high-pressure pipelines and marine pipelines. Corrosion of the internal and external parts of pipes is the main factor in failure of pipelines. Aggressive environments and places of their action will cause different types of corrosion. During the operation of low-carbon pipe steels, their corrosion rate was investigated under different operational parameters and environments. The main results of many researchers do not always coincide with each other, and therefore the comparison of corrosion rates for pipe steels of different generations is relevant today. The influence of aggressive environments on the corrosion rate of low-carbon steels of different generations was studied, with possible consideration of similar operating parameters and types of these environments. Different electrochemical parameters for all generations of steels are compared. The most sensitive parameters of corrosion resistance, which respond to the difference in environments and pipe materials, have been determined. It was found that a more aggressive environment and extreme operating characteristics for different steels give a clearer difference in determining the rate of corrosion. It was established that for a more aggressive environment, the difference in the rate of corrosion for different steels becomes more significant. The best indicators of corrosion resistance in various aggressive environments were shown by X70 and X80 steels, while X80 steel is the leader in corrosion resistance in many studies. Steel 17G1C, as expected, showed the worst indicators. Steels of the new generation X100 and X120 showed a worse level of corrosion rate than steel X80, but the best strength indicators are the main factor in their selection as pipeline materials that work in critical conditions.
Keywords: pipe steels; corrosion of metals; gas and oil pipelines; electrochemical parameters; corrosion rate; corrosion permeability